The chloroplast genome of Utricularia reniformis sheds light on the evolution of the ndh gene complex of terrestrial carnivorous plants from the lentibulariaceae family - Silva, Saura R. [UNESP]; Diaz, Yani C.A. [UNESP]; Penha, Helen Alves [UNESP]; Pinheiro, Daniel G. [UNESP]; Fernandes, Camila C. [UNESP]; Miranda, Vitor F.O. [UNESP]; Michael, Todd P.; Varani, Alessandro M. [UNESP] (Public Library of Science (PLoS), 2016)
Lentibulariaceae is the richest family of carnivorous plants spanning three genera including Pinguicula, Genlisea, and Utricularia. Utricularia is globally distributed, and, unlike Pinguicula and Genlisea, has both aquatic and terrestrial forms. In this study we present the analysis of the chloroplast (cp) genome of the terrestrial Utricularia reniformis. U. reniformis has a standard cp genome of 139,725bp, encoding a gene repertoire similar to essentially all photosynthetic organisms. However, an exclusive combination of losses and pseudogenization of the plastid NAD(P)H-dehydrogenase (ndh) gene complex were observed. Comparisons among aquatic and terrestrial forms of Pinguicula, Genlisea, and Utricularia indicate that, whereas the aquatic forms retained functional copies of the eleven ndh genes, these have been lost or truncated in terrestrial forms, suggesting that the ndh function may be dispensable in terrestrial Lentibulariaceae. Phylogenetic scenarios of the ndh gene loss and recovery among Pinguicula, Genlisea, and Utricularia to the ancestral Lentibulariaceae cladeare proposed. Interestingly, RNAseq analysis evidenced that U. reniformis cp genes are transcribed, including the truncated ndh genes, suggesting that these are not completely inactivated. In addition, potential novel RNA-editing sites were identified in at least six U. reniformis cp genes, while none were identified in the truncated ndh genes. Moreover, phylogenomic analyses support that Lentibulariaceae is monophyletic, belonging to the higher core Lamiales clade, corroborating the hypothesis that the first Utricularia lineage emerged in terrestrial habitats and then evolved to epiphytic and aquatic forms. Furthermore, several truncated cp genes were found interspersed with U. reniformis mitochondrial and nuclear genome scaffolds, indicating that as observed in other smaller plant genomes, such as Arabidopsis thaliana, and the related and carnivorous Genlisea nigrocaulis and G. hispidula, the endosymbiotic gene transfer may also shape the U. reniformis genome in a similar fashion. Overall the comparative analysis of the U. reniformis cp genome provides new insight into the ndh genes and cp genome evolution of carnivorous plants from Lentibulariaceae family.